PENGARUH MEDIA HOPSCOTCH RING TERHADAP KEMAMPUAN GERAK LOKOMOTOR ANAK DI TAMAN KANAK-KANAK DARUL FALAH PADANG - Shaniyah Aulia Putri; Indra Yeni; Farida Mayar; Tisna Syafnita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is based on observations showing that children's locomotor skills at Darul Falah Kindergarten, Padang, have not yet developed optimally. This is indicated by the children's low ability to maintain balance, hop on one leg, and lack of agility when walking and running. The purpose of this study was to determine the effect of the hopscotch ring on children's locomotor skills at Darul Falah Kindergarten, Padang. This study was quantitative with a quasi-experimental method. The study population was all children at Darul Falah Kindergarten, Padang. The sampling technique used purposive sampling, with B1 selected as the experimental class and B3 as the control class, with 13 children in each class. Data were collected through testing, documentation, and observation. Data analysis included normality tests, homogeneity tests, and hypothesis tests. The data were then processed using a t-test. Based on the research results, the average pre-test score for the experimental class was 15.07, while the average post-test score was 21.46. The average pre-test score for the control class was 14.07 and the average post-test score for the control class was 18.15. A t-test was then conducted, with a value less than the 0.05 criterion, namely 0.003. Thus, there was a significant difference between the experimental and control classes. The results of this study indicate that the use of hopscotch rings has an effect on the locomotor skills of early childhood. Keywords: Early Childhood, Locomotor Skills, Hopscotch Ring